Defect enriched N-doped carbon nanoflakes as robust carbocatalysts for H2S selective oxidation. Issue 18 (25th March 2020) - Li, Shiyan; Gu, Qingqing; Cao, Ning; Jiang, Qian; Xu, Chi; Jiang, Chengfa; Chen, Congmei; Pham-Huu, Cuong; Liu, Yuefeng
Abstract : The rational designed defect enriched N-doped nanocarbons present superior activity and stability for H2 S selective oxidation. Abstract : Nanocarbons have emerged as low-cost, efficient and durable nonmetallic catalysts for H2 S selective oxidation. However, the most efficient active sites for H2 S activation remain elusive, which restricts further development of high-performance catalysts for industrial application. Herein, we report on the synthesis of N-doped carbon nanoflakes with tunable nitrogen dopants and abundant structural defects for H2 S selective oxidation. These defect enriched N-doped carbon nanoflakes exhibited significantly enhanced catalytic performance (>740 gsulfur kgcat. −1 h −1 ), stability (>110 h) and decent tolerance to impurity gas (CO2 ) and steam toward continuous H2 S selective oxidation. Combined advanced characterization, control experiments and theoretical simulation showed that the N species along with defects on N-doped carbon nanoflakes could enhance significantly the catalytic activity, and further confirmed that the pyridinic N was the most active species and the C atoms adjacent to N atoms exhibit strong interaction with HS − . Our study provides predictive guidelines for the rational design of highly efficient and durable carbocatalysts for continuous catalytic oxidative desulfurization.